SOSIALISASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS BUDAYA CIANJUR DI SMP ISLAM AT-TAQWA - Rani Sugiarni; Erwan Setiawan; Neneng Pitaloka Kusumah Putri (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
Learning mathematics becomes difficult learning and is not in demand by students. faced by At-Taqwa Islamic Junior High School students on algebraic material, especially in understanding concepts. Teachers have not provided meaningful experiences in their learning through a mathematical approach to local culture. Implementation methods used: 1) Preparation, 2) Implementation, and 3) Evaluation. The results of the implementation of the Student Response Questionnaire Data Analysis on Learning with the Application of the Cianjur Culture-Based Problem Based Learning (PBL) Model stated that the student's response was positive because the average proportion of student responses in each aspect was 99% and this met the predetermined criteria.